Experimental Study of Gas Explosions in Hydrogen Sulfide-Natural Gas-Air Mixtures - André Vagner Gaathaug; Dag Bjerketvedt; Knut Vaagsaether; Sandra Hennie Nilsen (Journal of Combustion)
An experimental study of turbulent combustion of hydrogen sulfide (H2S) and natural gas was performed to provide reference data for verification of CFD codes and direct comparison. Hydrogen sulfide is present in most crude oil sources, and the explosion behaviour of pure H2S and mixtures with natural gas is important to address. The explosion behaviour was studied in a four-meter-long square pipe. The first two meters of the pipe had obstacles while the rest was smooth. Pressure transducers were used to measure the combustion in the pipe. The pure H2S gave slightly lower explosion pressure than pure natural gas for lean-to-stoichiometric mixtures. The rich H2S gave higher pressure than natural gas. Mixtures of H2S and natural gas were also studied and pressure spikes were observed when 5% and 10% H2S were added to natural gas and also when 5% and 10% natural gas were added to H2S. The addition of 5% H2S to natural gas resulted in higher pressure than pure H2S and pure natural gas. The 5% mixture gave much faster combustion than pure natural gas under fuel rich conditions.